History and Symbolic Anthropology: A Review and Critique of Four New Contributions to their Rapprochement - McCracken, Grant (Culture, 1983)
This paper examines the most recent attempt to incorporate an historical approach within anthropology. Following a well established disciplinary tradition, symbolic anthropology is only now, relatively late in its career, beginning to address historical problems and methods. This paper considers the efforts of Geertz, Wallace, Turner and Sahlins to give symbolic anthropology an historiographic competence and application. It is argued that three of them (Geertz, Wallace and Turner) fail in different ways to devise a notion of structure capable of successfully treating the facts of change and innovation. It is also argued that Sahlins enjoys greater success in this effort, but that his work must be supplemented with a concept of historical process. One such concept is proposed.